Bibliografi over Rosenius’ skrifter udgivet på dansk - Kofod-Svendsen, Flemming (Kirkehistoriske Samlinger, 2014)
Den svenske vækkelsesleder, præstesønnen Carl Olof Rosenius (1816-1868) har haft stor indflydelse på dele af dansk kirkeliv. Dette skyldes ikke mindst hans skrifter, der i stort tal er blevet oversat til dansk. I denne artikel gives et overblik over Rosenius’ skrifter. Den begynder med en skitse over hans liv og over den svenske forskning om hans teologi, ligesom den i hovedlinjer opridser de svenske udgivelser af hans skrifter, eftersom de danske udgivelser især er kommet fra Sverige. Dog er nogle skrifter kommet fra Norge. Derfor beskrives i kort form også rosenianismen i Norge med forskning om Rosenius og udgivelse af hans skrifter på norsk. Oversigten over skrifter af Rosenius i Sverige og Norge er ikke en udtømmende bibliografi. Eftersom udgivelsen af Rosenius’ skrifter i Danmark hovedsagelig er sket fra Bornholm, gives en beskrivelse af baggrunden for dette. Tyngdepunktet i artiklen er bibliografien over skrifter af Rosenius udgivet på dansk. Dernæst nævnes, at skrifter af Rosenius også er udgivet på Færøerne med dansk inspiration. Som afslutning omtales en række sprog, som Rosenius’ skrifter er oversat til. Summary Bibliography of Rosenius’ writings in Danish The Swedish revivalist C.O. Rosenius was the editor of the devotional magazine Pietisten from 1842 till his death. In the years 1842-59 he wrote a large number of devotional articles based on texts of his own choice. In the years 1860-66 the main content of Pietisten was Rosenius’ exposition of Letter to the Romans. From 1867 till his death in 1868 Rosenius wrote sermons and explanatory notes for sermons. All these articles were published in a number of booklets and major books in Swedish and were subsequently translated into many languages – partly as collected works, partly as independent writings and finally as a number of booklets. Several scholars have published scholarly dissertations in which they describe and study Rosenius’ preaching and consider his importance for church history.’ The first booklet to appear in Danish was Din Besøgelses-Tid from 1856. In the years 1856-1969 48 different booklets were published in a total of 98 prints. In the years 1866-1879 Chr. Møller (1834-1907), the founder of Luthersk Mission, translated the devotional articles from Pietisten and published them under the title Hemmeligheder i Lov og Evangelium in four volumes – approximately 2.000 pages. In the years 1868-1916 a number of reprints appeared. After Rosenius in 1866 had finished his exposition of Letter to the Romans, the commentary was published in Stockholm in 1867-68 in two volumes of 728 and 535 pages respectively. In 1874-1933 there were three reprints of a Danish edition of Letter to the Romans, the commentary was translated into Danish by Associate Professor, Dr C. Rosenberg on the basis of a Norwegian translation. In the years 1881-1995 four books, with an average page number of 200, appeared in nine reprints. Like the booklets they consisted of articles from Pietisten, but here several articles were gathered in each book. In the year 1885 a volume of sermons by Rosenius from Pietisten 1867-68 was published. The volume was reprinted in 1909. In 1935 Betragtninger til hver dag i Aaret. Uddrag af C.O. Rosenius’ Skrifter, a devotional book for use in the home, appeared. The years 1948-2009 revealed four new editions, one of them a marked linguistic adaption and very abridged too. In the years 1939-99 three different devotional books for young people in 11 reprints were published. All were brief excerpts from the devotional book Betragtninger til hver dag i Aaret. In the years 1950-57 Rosenius’ Collected Works in 15 volumes, translated from Pietisten appeared. The content was the same as Hemmeligheder i Lov og Evangelium. In 1978 Vejledning til fred was published; it had been reprinted many times in Norwegian since 1874. It was reissued in 1989 and 2006. In 1986 Berørt af Gud was published. It consisted of a number of articles from Collected Works which had been shortened and »diluted« in order to facilitate the reading. In the years 1998-2002 the Collected Works from the 1950es were abridged and adapted to modern Danish and published in eight volumes.